A phenotypically diverse family with an atypical 22q11.2 deletion due to an unbalanced 18q23;22q11.2 translocation. Issue 5 (11th February 2021) - Peter, Beate; Scherer, Nancy; Liang, Winnie S.; Pophal, Stephen; Nielsen, Colby; Grebe, Theresa A.
Abstract: The 22q11.2 deletion syndrome (22q11.2 DS) is the most common deletion syndrome in humans. In most cases, it occurs de novo . A rare family of three with 22q11.2 deletion syndrome (22q11.2 DS) resulting from an unbalanced 18q;22q translocation is reported here. Their deletion region is atypical in that it includes only 26 of the 36 genes in the minimal critical 22q11.2 DS region but it involves the loss of the centromeric 22q region and the entire p arm. The deletion region overlaps with seven other rare atypical cases; common to all cases was the loss of a region including SEPT5‐GP1BB proximally and most of ARVCF distally. Interrogation of the deleted 22q region proximal to the canonical 22q11.2 deletion region in the DECIPHER database showed seven cases with isolated or combined traits of 22q11.2 DS, including three with clefts. The phenotypes in the present family thus may result from the loss of a subset of genes in the critical region, or alternatively the loss of other genes or sequences in the proximal 22q deletion region, or interactive effects among these. Despite the identical deletion locus in the three affected family members, expression of the 22q11.2 DS traits differed substantially among them. These three related cases thus contribute to knowledge of 22q11.2 DS in that their unusual deletion locus co‐occurred with the cardinal features of the syndrome while their identical deletions are associated with variable phenotypic expression.